(untitled) (Informatica, 2014)
To support the interoperability or the cooperation between different partners, various approaches and technological solutions were proposed, which converge directly to the adoption of standards. Consequently, the semantic aspect is not correctly addressed by today’s interoperability solutions that focus mainly on the syntactical and technical level. Indeed, addressing the semantic aspect at conceptual level will provide more flexibility to the cooperation. Accordingly, in this paper, we propose an agnostic approach for the interoperability of Workflow models (or business process), which is used in a homogeneous or in a heterogeneous context. In a homogeneous context, lexical and structural annotations are attached to models. Contrary, in a heterogeneous context, we introduce a common semantic annotation structure for annotating the models at different levels: 1) meta-models, 2) models content, 3) models profiles and goals for semantic discovery purposes, 4) at levels of basic aspects of models such as the informational type. Common ontologies, including: Workflow ontology, domain specific ontology, profiles ontology, goals ontology and a set of ontologies related to these aspects, are used to achieve semantic interoperability. One of the advantages of this proposal is its flexibility and its openness since we take an agnostic approach to ontology representation languages (such as OWL-S or WSDL-S).